Assessment of implementation challenges of electronic medical record in Yekatit 12 hospital medical college - Abiyot Alemu Mamae; Ephrem Mamo (PLoS ONE, 2025)
Background The implementing challenges of Electronic Medical Records (EMR) refer to the difficulties and obstacles faced by healthcare organizations during the process of implementing and integrating electronic medical record systems into their operations. Research indicates that understanding the specific obstacles faced by healthcare organizations in implementing EMR is crucial for effective intervention strategies. Therefore, this study aims at assessing the implementation challenges of EMR. Methods A cross sectional study design with quantitative and qualitative approach was employed in Yekatit 12 hospital medical college (Y12HMC). A structured and pre-tested questionnaire was used to analyse socio-demographics, knowledge, perceived benefits and usefulness, and challenges of EMR implementation. Descriptive statistics was employed to summarise the quantitative data. Qualitative data was thematically presented. Result In this study 389 participants were surveyed with a response rate of 92.2%. Of the respondents, 54.4% had 1–5 service years, and 45% had no prior EMR system training. According to 89.7% of participants EMR improves practice productivity, and more secure than paper-based systems for storing patient records. Poor project management (62%), less eye contact with clients (57.6%), low users acceptance (55%), slow EMR system (45%), long waiting time for consultation (42.7%), lack of training and follow up (38%), high cost for wrong/repeated lab request (35.5%) and loss of privacy (33.2%) are challenges of implementation of EMR. The majority of the participants hold favorable perceptions and willing to use the system. Conclusion The most common challenges for EMR implementation in Y12HMC are poor project management, less eye contact by physicians with clients, low users acceptance, lack of training and follow up and long waiting time for consultation. The majority of participants hold favorable perceptions and willing to use the system.